Navigating Technological Disruption: Enhancing School Human Resources through Digital Literacy and Digital Citizenship - Alif Luthvi Azizah; Devi Sutrisno Putri; Sheren Dwi Oktaria (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The rapid advancement of information technology has transformed the education sector and requires school human resources to possess digital literacy and digital citizenship competencies. This community service program, conducted at SMP YPPL Panjang in Bandar Lampung City, aimed to strengthen teachers’ understanding of these competencies as an effort to improve the quality of school human resources. The program adopted a learning-by-doing approach involving knowledge sharing, discussions, practical activities, and an initial assessment through questionnaires. The findings revealed that most participants were already familiar with the concepts of digital literacy and digital citizenship; however, they had not fully recognized their strategic role in addressing the challenges of technological disruption in education. At the end of the program, 100% of participants signed a commitment statement to pursue continuous self-development, implement digital citizenship values, act as change agents, and foster sustainable collaboration. These findings highlight the importance of strengthening digital literacy and digital citizenship as key foundations for preparing school human resources to adapt to technological changes and support the development of a high-quality, inclusive, and sustainable educational ecosystem.